Konstruk Teori dan Paradigma Pengetahuan - M, Marilang; N, Nurhaerat (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to explain, analyze and understand the theoretical construct of the philosophy of science paradigm. The type of research used is data collection techniques, library research, which examines, searches for and collects information from various sources. Basically, a theory is formulated to explain existing phenomena. Building a theory which is an abstract of a number of concepts agreed upon in definitions will experience development, and this development occurs when the theory is no longer relevant and no longer functions to solve problems. Acceptance of a theory in the scientific community does not mean that the theory has absolute truth. Every theory is always influenced by the assumptions and methods of the scientist who formulated it. The ability of a theory to predict what will happen is a criterion for the validity of the theory. Therefore, it is necessary to understand theoretical constructs as a basis for scientific research.